ROBOT CONTROL DEVICE - TAKAHASHI, Yuutarou; NAMIKI, Yuta (2024)
This robot control device for controlling a robot comprises: a storage unit that stores a first imaging position for performing, by means of a visual sensor mounted to the robot, a stereoscopic measurement on a subject installed in a work space, and a second imaging position for performing a stereoscopic measurement on the subject by means of the visual sensor, the second imaging position having a larger parallax than that of the stereoscopic measurement performed at the first imaging position; a first measurement unit that performs the stereoscopic measurement on the subject at the first imaging position and acquires a first deviation amount of the robot with respect to the work space; a correcting unit that, on the basis of the first deviation amount, corrects the position of the robot during the stereoscope measurement at the second imaging position; a second measurement unit that performs the stereoscopic measurement of the subject at the second imaging position and acquires a second deviation amount of the robot with respect to the work space; and an action control unit that corrects an action of the robot on the basis of the second deviation amount. Ce dispositif de commande de robot destiné à commander un robot comprend : une unité de stockage qui stocke une première position d'imagerie destinée à réaliser, au moyen d'un capteur visuel monté sur le robot, une mesure stéréoscopique sur un sujet installé dans un espace de travail, et une seconde position d'imagerie destinée à réaliser une mesure stéréoscopique sur le sujet au moyen du capteur visuel, la seconde position d'imagerie présentant une parallaxe plus grande que celle de la mesure stéréoscopique réalisée au niveau de la première position d'imagerie ; une première unité de mesure qui réalise la mesure stéréoscopique sur le sujet au niveau de la première position d'imagerie et acquiert une première quantité d'écart du robot par rapport à l'espace de travail ; une unité de correction qui, sur la base de la première quantité d'écart, corrige la position du robot pendant la mesure de stéréoscope au niveau de la seconde position d'imagerie ; une seconde unité de mesure qui réalise la mesure stéréoscopique du sujet au niveau de la seconde position d'imagerie et acquiert une seconde quantité d'écart du robot par rapport à l'espace de travail ; et une unité de commande d'action qui corrige une action du robot sur la base de la seconde quantité d'écart. ロボットを制御するためのロボット制御装置であって、ロボットに搭載した視覚センサにより作業空間に設置された対象に対するステレオ計測を行うための第１撮像位置と、視覚センサにより対象に対するステレオ計測を行うための第２撮像位置であって第１撮像位置でのステレオ計測よりも視差が大きくなる第２撮像位置とを記憶する記憶部と、第１撮像位置で対象のステレオ計測を行い、作業空間に対するロボットの第１ずれ量を取得する第１計測部と、第１ずれ量に基づき第２撮像位置でのステレオ計測時のロボットの位置を補正する補正部と、第２撮像位置で対象のステレオ計測を行い、作業空間に対するロボットの第２ずれ量を取得する第２計測部と、第２ずれ量に基づいてロボットの動作を補正する動作制御部と、を備えるロボット制御装置である。